2006
DOI: 10.2134/agronj2005.0174
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and Tillage Effects on Irrigated Continuous Corn Yields

Abstract: A no-till (NT) production system has potential to reduce soil erosion, fossil fuel consumption, and greenhouse gas emissions compared with a conventional till (CT) system. Nitrogen fertilization (four to six N rates) and tillage system (CT and NT) effects on irrigated, continuous corn (Zea mays L.) yields were evaluated for 5 yr on a clay loam soil to determine the viability of the NT system and N needs for optimum yield. Corn in both NT and CT systems responded similarly to available N supply. Grain yields we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
94
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 23 publications
(25 reference statements)
19
94
0
1
Order By: Relevance
“…It was consistent with other studies (Halvorson et al, 2005;Gagnon and Ziadi, 2010). Halvorson et al (2005) reported a significant increase in grain yields with rates up to 224 kg N ha -1 under irrigated conditions. Ma et al (2005) observed that corn grain yields increased significantly with rates up to 120 kg N ha .…”
Section: Discussionsupporting
confidence: 93%
“…It was consistent with other studies (Halvorson et al, 2005;Gagnon and Ziadi, 2010). Halvorson et al (2005) reported a significant increase in grain yields with rates up to 224 kg N ha -1 under irrigated conditions. Ma et al (2005) observed that corn grain yields increased significantly with rates up to 120 kg N ha .…”
Section: Discussionsupporting
confidence: 93%
“…Grain yields were measured at physiological maturity in late October to early November each year by hand harvesting two rows 7.6 m long per plot. Plot management details for the study are provided in Halvorson et al (2004Halvorson et al ( , 2006.…”
Section: Materials and Methods Site Descriptionmentioning
confidence: 99%
“…In 2012, lower, but still very high, R 2 values of 0.81, 0.87, and 0.97 were observed for rainfed, 75% FIT, and FIT, respectively. The weaker regression responses were due to the inclusion of control (0 kg Halvorson et al (2006) compiled five years of data and found a curvilinear increase in CWUE with increasing N availability under both conventional and no-till practices. Similar results were found by Carlson et al (1959), Viets (1962), Olson et al (1964), andAl-Kaisi andYin (2003).…”
Section: Treatment Effects On Cwuementioning
confidence: 99%